2013
DOI: 10.1093/intqhc/mzt069
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarks for acute stroke care delivery

Abstract: ObjectiveDespite widespread interest in many jurisdictions in monitoring and improving the quality of stroke care delivery, benchmarks for most stroke performance indicators have not been established. The objective of this study was to develop data-derived benchmarks for acute stroke quality indicators.DesignNine key acute stroke quality indicators were selected from the Canadian Stroke Best Practice Performance Measures Manual.ParticipantsA population-based retrospective sample of patients discharged from 142… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…Description of the audit sampling strategy and a complete breakdown of exclusions is reported elsewhere [14]. …”
Section: Methodsmentioning
confidence: 99%
“…Description of the audit sampling strategy and a complete breakdown of exclusions is reported elsewhere [14]. …”
Section: Methodsmentioning
confidence: 99%
“… HNHB Hamilton Niagara Haldimand Brant, LHIN Local Health Integration Network, N/A Not Applicable, SU Stroke Unit, TIA Transient Ischemic Attack a Data source: Ontario Stroke Evaluation Report 2014 [17]…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, all 32 identified SUs had a geographically defined location, and the majority were based in a general medicine ward with a median of 13 beds. At the time of the survey, Canadian recommendations did not require SUs to be exclusive to stroke patients, nor have all of the resources in place; however, recommendations did require SUs to be in one geographic location [17]. Later in 2014, the OSN revised the definition of SUs, which included additional criteria related to bed allocation and staff.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations